1996
DOI: 10.1163/156856896x00123
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the locations of spatial features and those of fixations made during visual examination of briefly presented images

Abstract: The locations of features such as extremes of contrast or luminance, high spatial frequency content and edge density in a set of images have been determined, and the locations of fixations made by a group of eighteen human observers who examined the images during brief (3 s) presentations were also measured. The similarity between the locations of the eye movements and those of each stimulus feature was determined by means of a least squares index IS. For averages taken over data for all observers, the similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(63 citation statements)
references
References 0 publications
2
60
1
Order By: Relevance
“…Furthermore, landing position influenced fixation time: The duration of the first fixation on an object decreased and the probability of refixating an object increased as the deviation of the initial landing position from the center of the object increased. Mannen et al (1995Mannen et al ( , 1996Mannen et al ( , 1997 had viewers look at normal scenes or the scenes after they had been either high-pass or low-pass filtered. They found that viewers looked in pretty much the same locations across the three versions of the scene.…”
Section: Eye Movement Controlmentioning
confidence: 99%
“…Furthermore, landing position influenced fixation time: The duration of the first fixation on an object decreased and the probability of refixating an object increased as the deviation of the initial landing position from the center of the object increased. Mannen et al (1995Mannen et al ( , 1996Mannen et al ( , 1997 had viewers look at normal scenes or the scenes after they had been either high-pass or low-pass filtered. They found that viewers looked in pretty much the same locations across the three versions of the scene.…”
Section: Eye Movement Controlmentioning
confidence: 99%
“…Edge density was defined as the proportion of edge pixels within an image patch. Edge pixels were found by filtering the scenes with a Sobel operator that responds to contours in scenes represented by steep gradients in luminance (see Mannan et al, 1995Mannan et al, , 1996. Greater edge density is associated with image patches containing a greater number of contours.…”
Section: Scene Statistics Methodsmentioning
confidence: 99%
“…For example, high spatial frequency content and edge density have been found to be somewhat greater at fixated than non-fixated locations (Mannan, Ruddock, & Wooding, 1996, 1997b. Furthermore, local contrast (the standard deviation of intensity in a patch) is higher and two-point intensity correlation (intensity of the fixated point and nearby points) is lower for fixated scene patches than control patches (Krieger, Rentschler, Hauske, Schill, & Zetzsche, 2000;Parkhurst & Neibur, 2003;Reinagel & Zador, 1999).…”
Section: Fixation Placement During Scene Viewingmentioning
confidence: 99%
See 1 more Smart Citation
“…External factors are image immanent features, such as local image contrast and local image structure, which transiently attract eye gaze, independent of a particular task. Internal factors, such as an individual's attentional state, expectation, experience and memory, are top-down and task-dependent (Noton and Stark 1971;Mannan et al 1997;Henderson 2003). It is argued that in general, the initial saccade to an image is driven predominantly by external factors (Parkhurst et al 2002;Peters et al 2005), but can also be biased by internal factors (Henderson 2003).…”
Section: Introductionmentioning
confidence: 99%